Achieving Macroeconomic Goals - O'Brien, Mike (Review of Economic Studies, 1982)
Two basic approaches to using dynamic econometric models to formulate macroeconomic policy are generally in use. These are: invertible transfer function methodology and optimal control methodology. In this paper a technique for determining dynamic growth paths is presented. The result of the application of this technique is the synthesis of the two approaches into a single approach yielding a policy with more desirable characteristics than was previously possible. An example of the use of this synthesis technique using Pindyck's model is presented.